Mobile Banking and Security Challenges - Sasikumar, Dr.G. (International Journal of Scientific Research and Management (IJSRM), 2017)
Banking services have expanded from cash in the bank to internet banking and now mobile banking which attained broad recognition internationally. With help of mobile banking facilitates the customers access their accounts and entire information about bank products and services anywhere anytime through Internet and World Wide Web. The mobile banking is trustworthy, secured and cost effective, nevertheless complex and vulnerable to network problem. Security issues are significant since intruders makes others life as unsafe and miserable. One could be sufferer of a cyber crime in several ways. In this paper an effort is made to study the various security issue, challenges and solutions related to mobile banking services.